Massive fetal cardiac rhabdomyoma treated with transplacental sirolimus - McLoughlin, Zoetta; Kathol, Melanie; McIntosh, Amanda (Prenatal Cardiology, 2022)
Cardiac rhabdomyomas, the most common type of fetal cardiac tumor, can grow prenatally, in rare instances leading to heart failure and fetal demise. In severe cases, there have been reports of successful treatment with transplacental mechanistic target of rapamycin inhibitor (mTORi) therapy, specifically sirolimus. However, given the small number of published cases, the dosing regimen and safety profile of sirolimus in pregnancy for this indication remain undefined. This case details successful treatment with sirolimus therapy in a fetus with a massive septal cardiac rhabdomyoma leading to left ventricular cavity obliteration and left ventricular outflow tract (LVOT) obstruction with resulting fetal hydrops. A mother with a previous child with tuberous sclerosis complex presented for evaluation of rapidly enlarging fetal cardiac masses in the second trimester. Due to fetal hemodynamic compromise by 30 weeks gestational age (GA), the mother was initiated on oral sirolimus therapy. Two weeks after initiation of therapy, mass size and fetal hydrops had significantly improved. Oligohydramnios developed at 36 weeks GA, prompting delivery of a live-born infant appropriate for GA. Oligohydramnios has never been reported with maternal sirolimus use. With this case, we confirm previously described dosing regimens for treatment and describe the safety profile of sirolimus in pregnancy based on current national registry data. We also highlight the need for maternal and fetal monitoring after treatment initiation.